Alternative Mechanisms Guiding Salespersons' Ambidextrous Product Selling. (4th December 2015) - van der Borgh, Michel; de Jong, Ad; Nijssen, Edwin J.
Abstract : Ambidextrous product‐selling strategies, in which companies' salespeople concurrently pursue the sale of existing and new products, are hard to implement. Previous studies have addressed this issue for relatively simple consumer settings with the manager in close proximity to the salespersons and focusing on different levels of control and autonomy to resolve this issue. However, little is known about how field salespeople can be influenced to pursue such dual goals proactively for more complex business‐to‐business products. In this study, the authors distinguish between salespeople's proactive selling behaviour for new and existing products, and study the impact of two alternative mechanisms: a situational mechanism (i.e. perceived manager product‐selling ambidexterity) and a structural mechanism (i.e. salesperson organizational identification). Using a time‐lagged, multisource data set from a large ambidextrous company, the authors demonstrate that both mechanisms contribute to salespeople's proactive selling of new and existing products, but also act as each other's substitutes. The results suggest two most likely strategies for salespeople to obtain overall sales targets: focusing on existing product selling; or acting ambidextrously. The latter approach offers the benefits of better achieving ambidextrous company sales goals and of greater performance stability, and is thus preferred.